AVALIAÇÃO DO CONSUMO ALIMENTAR DE GESTANTES ADOLESCENTES DE DUAS UNIDADES DE SAÚDE DO OESTE DE SANTA CATARINA - Zat, Andrieli; De Carli, Eliane (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
The growth of teenage pregnancy is seen with concern by the public health area, highlighting the need for attention to this age group of the population. The consumption of foods that meet the demand for nutrients has been identified as one of the important components of pregnancy. This work aims to analyze the food consumption of pregnant teenagers, attended in basic health units, and correlate with their socioeconomic factor. The study was applied in the municipalities of Iraceminha and Maravilha. The study sample is composed of pregnant teenagers from the two municipalities, seven from the municipality of Iraceminha and eight from the municipality of Maravilha, aged between fourteen and twenty years. Data collection was performed virtually and questionnaires had socioeconomic assessment and frequency of food consumption. Most pregnant women were between 16 and 18 years of age, living in a stable relationship, had completed high school or are in higher education. Excess weight was high among pregnant women, which indicates that the lack of care in eating, most pregnant women did not change their eating habits during pregnancy. Among the foods that are not good during pregnancy, soft drinks, fried foods, sweets, artificial juice, sugar, margarine and cookies were mentioned.